FACTORS AFFECTING THE DELAYED COLLECTIBLES LAND AND BUILDING TAX FOR THE SURAKARTA SOCIETIES - Supriyono .; Dibyo Iskandar (BHIRAWA, 2013)
This study aimed to examine the effect of taxpayers behavior, the tax officials behavior, the imposition of fines and Nahdatul Ulama’s fatwa against the delayed of collectibles property taxes for the people of Surakarta. The data were collected by distributing questioners and tested with testing instruments which include the validity and reliability as well as the classical assumption. Method of analyzing the data used a multiple regression analysis, t- test, f-test and R2test. T test results obtained that the variable of tax payers’ behavior, the behavior of tax officials, the imposition of fines, the NU fatwa had a significant influenced to the delayed of the collectibles of land and building tax. F-test results obtained that there was a significant relationship between the independent variables toward a dependent variable. And R2 test results obtained that the free variables had a positive contribution toward a dependent variable 65,5%, the remaining 34,5% was influenced by other factors outside of the variables studied. Keywords: Taxpayers behavior, tax officials’ behavior, the imposition of fines, Nahdlatul Ulama’s fatwa.